IMPLEMENTASI CASE BASED REASONING PENYAKIT SAPI DENGAN METODE NEAREST NEIGHBOR BERBASIS WEB - LUKITO, ADAM; Nur Wahyudi, Eko (Information Technology and Telematics, 2018)
Abstract- Cattle is one of the livestock commodities that become the mainstay of the source of animal protein in the form of meat and milk which is quite familiar in the community. In cattle raising, one of the most common constraints is disease. In fact, not infrequently breeders experience losses and no longer livestock due to death in livestock. Healthy cows are usually characterized by the condition in the body of the cattle is functioning properly. Conditions in which the flow of fluid in the body works well in support of the preparation of important cells in it. With regular attention to the condition of the cow and the environment and quick response sehinggan cows will always healthy and normal. System development method used in this research is expert system consisting of identification, conceptualization, formalization, implementation with PHP and MySQL, evaluation. The final result of this research is the implementation of Case Based Reasoning of cow disease with Nearest Neighbor web-based method to produce the final value of similarity between 0 (zero) to 1 (one) and able to provide solution from cow disease